Dissecting the gene expression, localization, membrane topology, and function of the plasmodium falciparum STEVOR protein family - Wichers, J. Stephan; Scholz, Judith A.M.; Strauss, Jan; Witt, Susanne; Lill, Andrés; Ehnold, Laura Isabell; Neupert, Niklas; Liffner, Benjamin; Lühken, Renke; Petter, Michaela; Lorenzen, Stephan; Wilson, Danny W.; et al. (Mbio, 2019)
During its intraerythrocytic development, the malaria parasite Plasmodium falciparum exposes variant surface antigens (VSAs) on infected erythrocytes to establish and maintain an infection. One family of small VSAs is the polymorphic STEVOR proteins, which are marked for export to the host cell surface through their PEXEL signal peptide. Interestingly, some STEVORs have also been reported to localize to the parasite plasma membrane and apical organelles, pointing toward a putative function in host cell egress or invasion. Using deep RNA sequencing analysis, we characterized P. falciparum stevor gene expression across the intraerythrocytic development cycle, including free merozoites, in detail and used the resulting stevor expression profiles for hierarchical clustering. We found that most stevor genes show biphasic expression oscillation, with maximum expression during trophozoite stages and a second peak in late schizonts. We selected four STEVOR variants, confirmed the expected export of these proteins to the host cell membrane, and tracked them to a secondary location, either to the parasite plasma membrane or the secretory organelles of merozoites in late schizont stages. We investigated the function of a particular STEVOR that showed rhoptry localization and demonstrated its role at the parasite-host interface during host cell invasion by specific antisera and targeted gene disruption. Experimentally determined membrane topology of this STEVOR revealed a single transmembrane domain exposing the semiconserved as well as variable protein regions to the cell surface. IMPORTANCE Malaria claims about half a million lives each year. Plasmodium falciparum, the causative agent of the most severe form of the disease, uses proteins that are translocated to the surface of infected erythrocytes for immune evasion. To circumvent the detection of these gene products by the immune system, the parasite evolved a complex strategy that includes gene duplications and elaborate sequence polymorphism. STEVORs are one family of these variant surface antigens and are encoded by about 40 genes. Using deep RNA sequencing of blood-stage parasites, including free merozoites, we first established stevor expression of the cultured isolate and compared it with published transcriptomes. We reveal a biphasic expression of most stevor genes and confirm this for individual STEVORs at the protein level. The membrane topology of a rhoptry-associated variant was experimentally elucidated and linked to host cell invasion, underlining the importance of this multi-functional protein family for parasite proliferation.
CRIS-Team Scopus Importer:2019-08-16
Keywords: Host cell invasion; Malaria; Variant surface antigens